(untitled) (Damu Journal of Sport Sciences, 2025)
The large number of practical lessons, the burdens placed on students, and the lack of attention to muscle strengthening, warm-up operations, and other things are not limited to factors that lead to the occurrence of such injuries. The research aims to prepare intensive exercises using rubber ropes to rehabilitate the connective thigh muscles affected by second-degree tear among students of the College of Physical Education. and Sports Sciences - University of Baghdad and to identify its impact. The research assumes the presence of statistically significant differences, and that the research problem imposed on the researchers to use the experimental method, by designing a single experimental group with tests (pre-, inter- and post-tests) to suit the nature of the problem. As for the sample, they were selected intentionally and numbered (6) from students with a second degree tear in the College of Physical Education and Sports Sciences, University of Baghdad, and in various academic levels for the period between (01/12/2023) and (02/29/2024). The program was also used. (SPSS) to process the data statistically, and according to the results collected, they concluded that intensive exercises using rubber ropes had positive effects on the variables of the study within a short period, and they recommended using these exercises as guidance for rehabilitating those injured in sports and other injuries.